E se a cidade fosse queer: a construção de espaços inclusivos e contra-hegemônicos - Amador, Cristian Reginato (2024)
The concept of the city is examined in the light of social and technological advances, recognizing that modern cities are influenced by a neoliberalism that often marginalizes undesirable groups. This marginalization not only prevents the equitable occupation of urban space, but also perpetuates violence and discrimination, especially against the LGBTQIA+ population. Data from a 2022 report indicates an alarming increase in violence against this population, reflecting a discriminatory culture rooted in Brazilian society. With this in mind, the study sought to understand how it would be possible to think of a queer city, a city in which the occupation of spaces would also be possible for vulnerable groups and that accessibility to public policies could take place effectively in the face of the context of violence. In other words, by questioning these nuances, the proposed research seeks to explore the construction of a queer and participatory city, questioning the hegemonic norms that dominate urban space. It is divided into two stages: the first investigates the representations of urban space under gender violence and also from the premises of a neoliberal capitalism, while the second focuses on the conception of a queer city from the analysis of data collected from the LGBTQIA+ population. The theoretical approach is based on critical theory, especially the ideas of David Harvey, who suggests that the struggle for the right to the city should be central to urban emancipation and the critique of neoliberal capitalism. The research uses a dialectical method, confronting the theses about the ideal city and the hegemonic city, exploring how these dynamics affect urban occupation by marginalized groups. Comparative and typological methods are used to understand the complexity of urban space and develop ideal models of inclusive cities. The research technique encompasses bibliographic analysis and data collection through questionnaires, seeking to understand the experiences of LGBTQIA+ individuals in relation to urban space. The proposal argues that building a queer city is not just a demand for rights, but a form of resistance to the capitalist paradigm that perpetuates exclusion. This perspective criticizes the cultural hegemony that marginalizes certain identities and suggests that the transformation of urban space must be accompanied by a new approach to social relations, in which the voices of historically marginalized groups are effectively heard. In order to achieve what is proposed, the first step is to analyze the data that shows the scenario of violence perpetuated against the LGBTQIA+ population, so that, in a second step, it is possible to consider 1) the way spaces are built; 2) how performativity shapes the representation of spaces; and 3) how, based on the data collected, it would be possible to think of a reality in which the city is thought of from the precepts of queer theory as a complement to the participatory process of vulnerable groups in the structuring of urban policies.